2018
DOI: 10.4081/ecj.2018.7769
|View full text |Cite
|
Sign up to set email alerts
|

Trends of popularity of cardiac biomarkers: Insights from Google Trends

Abstract: This study was aimed at assessing the trend of worldwide popularity, thus likely reflecting usage, of conventional cardiac biomarkers, including cardiac troponins, myoglobin and creatine kinase MB (CK-MB). Google Trends was interrogated using a combination of the three search terms “troponin” AND “myoglobin” AND “CK-MB”, with a time limit set between January 1, 2014 (i.e., the oldest searchable year) and present time (i.e., August 13, 2018). The raw data were entered into an Excel worksheet and reported as cum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Google Trends is the most widely accessed tool in digital epidemiology that analyzes the popularity of top search queries on Google over time in different languages and geographic regions [7], [8]. Increasing or decreasing search volumes of a word in search engines is important in examining social behavior [9]. These platforms, which enable us to obtain epidemiological information promptly, are of critical importance in terms of early detection of situations that may put society at risk and taking prompt action.…”
Section: Introductionmentioning
confidence: 99%
“…Google Trends is the most widely accessed tool in digital epidemiology that analyzes the popularity of top search queries on Google over time in different languages and geographic regions [7], [8]. Increasing or decreasing search volumes of a word in search engines is important in examining social behavior [9]. These platforms, which enable us to obtain epidemiological information promptly, are of critical importance in terms of early detection of situations that may put society at risk and taking prompt action.…”
Section: Introductionmentioning
confidence: 99%
“…It has recently been demonstrated that assessment of Web-based inclinations, using tools such as Google Trends, reflects human behaviors along with preference to access some specific diagnostic and/or therapeutic resources [4], including the worldwide use of cardiac biomarkers [5]. Therefore, the results of this analysis suggests that, despite the existence of only one fully-automated Giuseppe Lippi, Fabian Sanchis-Gomar, Troponins popularity immunoassay for measuring cTnT, the current popularity of cardiac biomarkers seems to favor cTnT.…”
mentioning
confidence: 99%